Evaluasi 4 Varietas Tanaman Sorgum (Sorghum bicolor L. Moench) Ditinjau Dari Aspek Morfologi Tanaman - Fauzi, Moh Mimbar; Binti Khopsoh; Tika Fitria Wulan Afrilia; Lestariningsih; Anang Catur Sulaksono; Anifiatiningrum (Anoa: Journal of Animal Husbandry, 2026)
Sorghum (Sorghum bicolor L. Moench) is a promising alternative forage crop for ruminants due to its high photosynthetic efficiency and tolerance to drought and marginal lands. However, comparative studies evaluating morphological traits and productivity among superior mutant varieties remain limited. This study aimed to evaluate and compare four sorghum varieties (Bioguma, Numbu, Mandau, and Super) in terms of morphological characteristics. The experiment was conducted in paddy fields of Plaosan Village, Wates District, Kediri Regency, from August to October 2025, using a Randomized Complete Block Design (4 treatments and 5 replications). Morphological parameters (plant height, stem diameter, number of nodes, node length, and leaf number) were measured at 75 days after planting. Data were analyzed using ANOVA followed by Duncan's Multiple Range Test (DMRT) at 5% or 1% significance level. The results showed that the Bioguma variety exhibited superior performance across all observed parameters compared to the other three varieties. Mandau variety showed relatively shorter plant height. Stem diameter showed positive correlations with other morphological parameters. These findings indicate that the Bioguma variety has the greatest potential as a high-quality ruminant forage source based on its morphological and productivity advantages.